2007
DOI: 10.5465/amj.2007.28225983
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Influences of Leaders' Relational Embeddedness on Interorganizational Exchange

Abstract: Drawing on the concept of relational embeddedness and the associated mechanisms of mutual understanding, trust, and commitment, we examine how leaders' prior exchange experiences influence the likelihood of subsequent interorganizational exchange. We begin to develop a microlevel model of organization-level relations that accounts for nodal multiplexity. In data on baseball player trades, we found that individual leaders' ties affected exchanges less than did an organization's other ties. The sharing of exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 72 publications
2
77
0
5
Order By: Relevance
“…The embeddedness of organizations depends on ties at the level of individuals (Barden andMitchell 2007, Granovetter 1985). Ties at the level of organizations operate through individuals and their connections with counterparts in partner organizations (Seabright et al 1992), thus creating multiple levels of embeddedness (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The embeddedness of organizations depends on ties at the level of individuals (Barden andMitchell 2007, Granovetter 1985). Ties at the level of organizations operate through individuals and their connections with counterparts in partner organizations (Seabright et al 1992), thus creating multiple levels of embeddedness (cf.…”
Section: Introductionmentioning
confidence: 99%
“…While our primary objective was to construct a conservative measure for social ties, we are unable to analyze the interrelation between different levels of organizational and managerial social capital. Barden and Mitchell (2007), for example, combined interleader ties and organization-level ties in their analysis of interorganizatonal exchange and found that the influence of shared exchange experience between the leaders of two organizations on interorganizational exchange was larger, when other members of the organizations also shared a history of exchange experiences. The authors thus concluded that "leaders have more influence within their organizational context than in isolation" (p. 1440).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barden and Mitchell (2007) infer the degree of a firm's social embeddedness from its previous transactions with other firms, and from previous transactions between its manager and other managers. Therefore, their definition reflects the joint history between the involved parties.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations